Social identification and depression: A meta-analysis - Postmes, Tom; Wichmann, Lenka J.; Van Valkengoed, Anne M.; Van Der Hoef, Hanneke (European Journal of Social Psychology, 2019)
A meta-analysis of 76 studies (N = 31,016) examined the relationship between social identification and depression. Overall, individuals who identify highly with a group tend to report less depression (average rz = −.15). However, a large amount of variability between studies was observed. The 95% prediction interval, which indicates the true effect size that can be expected in future research, ranged from rz = −.50 to.19. The relationship between depression and social identification is more complex than previously assumed. Some variability is related to the social identification measure used. Studies that focused on identification with interactive groups (rz = −.28) had larger effect sizes than studies that focused on social categories (rz = −.11). Moreover, studies of non-stigmatized groups (rz = −.24) had larger effect sizes than studies of stigmatized groups (rz = −.10). In conclusion, the structure and social identity content of groups appear to play an important role in the relationship between depression and social identification.
Created from Fastlane, Scopus look-up
Keywords: depression; meta-analysis; social identification; social identity theory